CMR findings in patients referred for suspected myocarditis following mRNA-based COVID vaccination compared with pre-COVID myocarditis referrals: A single-centre observational study. (December 2022) - Seitz, Andreas; Rogers, Claire; Moutzoukis, Georgios; Oberli, Lisa; Ong, Peter; Bekeredjian, Raffi; Mahrholdt, Heiko
Abstract: Background: Vaccination is considered the key to overcome the COVID pandemic. For the first time mRNA-based vaccinations are used in humans. Case series suggested an increased risk of myocarditis after vaccination. This study sought to describe CMR findings in patients with suspected mRNA-vaccine associated myocarditis. Methods: A total of 33 consecutive patients referred for CMR work-up of suspected myocarditis associated with mRNA-based vaccination were included. A historical cohort of 135 consecutive patients referred for suspected myocarditis in the pre-COVID era served as control group. All patients underwent multi-parametric CMR including CINE and late gadolinium enhancement (LGE) imaging as well as parametric T1/T2 mapping of the left ventricular myocardium. Results: Patients referred for suspected vaccination-related myocarditis were more often female (55 % vs 32 %, p = 0.015) and demonstrated smaller LV dimensions as well as a better LV function compared to patients of the control group. CMR revealed a lower prevalence of non-ischemic LGE in patients with suspected vaccination-myocarditis (6 % vs 22 %, p = 0.04). However, among patients without LGE we observed a higher prevalence of an abnormal T1/T2 mapping result in patients with suspected vaccination-myocarditis compared to the control group (45 % vs 18 %, p = 0.010). Conclusion: In this small single-centre study, compared to myocarditis referrals in the pre-COVID era, patients currently referred for CMR work-up of suspected mRNA-vaccination-associated myocarditis demonstrated lower prevalence of LGE but higher prevalence of abnormal T1/T2 mapping. These hypothesis-generating observations may point towards a rather subtle myocardial damage and support the routine use of T1/T2 mapping in this indication.